Constitutionalising immigration law - Marzal, Elia (Managerial law, 2006)
This e-book examines the phenomenon of immigration and the legal responses to it by European Union states. The reasons for, and the specific process of, conferral of protection on immigrants raise questions which have been the subject of lengthy analysis and debate. Divided into two parts, this ebook first analyses the protection given to aliens in Germany, France and Spain, and goes on to evaluate these findings by deconstructing the process of conferral of protection.